Ground zero: not asthma at all. Issue 6 (September 2015) - de Benedictis, Fernando Maria; de Benedictis, Diletta; Mirabile, Lorenzo; Pozzi, Marco; Guerrieri, Arcangela; Di Pillo, Sabrina
Abstract Upper airway obstruction is commonly misdiagnosed as asthma. We report on four children with recurrent respiratory symptoms who had been erroneously diagnosed as having asthma and who received anti‐asthma medication for several years. The evaluation of spirometry tracing was neglected in all cases. Subglottic stenosis, tracheomalacia secondary to tracheo‐esophageal fistula, double aortic arch, and vocal cord dysfunction were suspected by direct inspection of the flow–volume curves and eventually diagnosed. The value of clinical history and careful evaluation of spirometry tracing in children with persistent respiratory symptoms is critically discussed.